A LIGHT ON THE EFFECT OF POMEGRANATE ON NEUROLOGICAL EVIDENCES OF PARKINSON’S DISEASE: A REVIEW - CHETIA, SWAPNALI; BORAH, GAURAB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Parkinson’s disease (PD) is a progressive neurodegenerative disease, in which the dopamine containing neurons gets degenerated in the SN region of ventral mid-brain. Various herbal or plant components have been tested in rodent models of Parkinson’s disease to understand its therapeutic effect. Recent progresses in therapeutic interventions against neurodegenerative disorders have shown the potential role of Pomegranate juice (PJ) as a promising neuroprotective agent. The fruit of pomegranate is a highly consumed all over the world and has proven its efficacy in many health beneficial aspects. PJ contains active ingredients mainly, ‘polyphenols’ which are found to be protective against the disease pathology of Alzheimer’s disease. A recent study demonstrated that PJ potentiate parkinsonian pathology in rodent. Meanwhile, PJ had shown neuroprotective effect in parkinsonian toxin induced cellular model. Thus, from the available literatures, no conclusion can be made whether PJ possess neuroprotective or neurodegenerative potential towards dopamine containing neurons in PD.As pomegranate juice has been recommended to possess medical benefit and is being used in daily diet, studying its potential benefits or side effect are of immense importance. Amending altogether, the therapeutic potency of pomegranate has been well evaluated and reported and the review had been forwarded to evaluate the diversified effects of pomegranate juice in Parkinson's disease.